Playworlds and Narratives as a Tool of Developmental Early Childhood Education - Hakkarainen P.; Bredikyte M. (Moscow State University of Psychology and Education, 2020)
We shortly introduce some main ideas of a project of scientific research collective "School" (Shkola) led by academic V.V. Davydov. The collective elaborated a new project - "Concept of preschool education" [9] that would better meet the developmental and educational needs of young children and create the basis for learning activity at school. The project has inspired development of playworld pedagogy in Sweden and Finland. Now 30 years later, attempts to design systems of developmental early childhood education try to concretize central concepts of Davydov's project. This article presents interpretation and elaboration of the main ideas of the project in playworld pedagogy developed in Scandinavian early childhood education. We propose a systematic transition from joint adult - children play, to independent children initiated play. Children's personality development presupposes esthetic reaction and contradictory unity of affect and intellect in narrative role play. We have concluded that present attempts to design new developmental early childhood education programs cannot forget the ideas of the collective from the 1990's.